Produção de lipases de Aspergillus niger e Aspergillus fumigatus através de fermentação em estado sólido, avaliação da especificidade do substrato e seu uso em reações de esterificação e alcoólise: evaluation of substrate specificity and use in esterification and alcoholysis reactions - Christian Oliveira Reinehr; Juliana Rizzardi; Marceli Fernandes Silva; Débora de Oliveira; Helen Treichel; Luciane Maria Colla (Química Nova, 2014)
Filamentous fungi were cultured under solid state fermentation of soybean residues to produce lipases. Enzymes produced by Aspergillus niger esterified oleic and butyric acids in the presence of ethanol, while enzymes produced by Aspergillus fumigatus demonstrated no esterification activity toward lauric acid. In case of A. niger, direct lyophilization of fermented bran led to higher esterification activity. The esterification of oleic acid by enzymes of A. fumigatus was neither influenced by pH adjustment nor by the extraction process. Conversions to ethyl esters were higher after pH adjustment with lyophilized liquid extract of A. niger.